Acute Adverse Events and Postoperative Complications in a Randomized Trial of Preoperative Short-course Radiotherapy Versus Long-course Chemoradiotherapy for T3 Adenocarcinoma of the Rectum: Trans-Tasman Radiation Oncology Group Trial (TROG 01.04). Issue 5 (May 2017) - Ansari, Nabila; Solomon, Michael J.; Fisher, Richard J.; Mackay, John; Burmeister, Bryan; Ackland, Stephen; Heriot, Alexander; Joseph, David; McLachlan, Sue-Anne; McClure, Bev; Ngan, Samuel Y.
Abstract : Objective: To compare acute adverse events (AE) and postoperative complication rates in a randomized trial of short-course (SC) versus long-course (LC) preoperative radiotherapy. Background: Evidence demonstrates that adding neoadjuvant radiotherapy to surgery offers better local control in the management of rectal cancer. With both SC and LC therapy there is a potential for acute treatment-related toxicity and increased patient morbidity. Methods: Eligible patients had clinical-stage T3 rectal adenocarcinoma within 12 cm of the anal verge with no evidence of metastasis. SC consisted of pelvic radiotherapy 5 × 5 Gy in 1 week, early surgery and 6 courses of adjuvant chemotherapy. LC was 50.4 Gy administered in 28 fractions during 5.5 weeks, with infusion 5-fluorouracil, surgery in 4 to 6 weeks, and 4 courses of chemotherapy. Results: All SC patients and 93% of LC patients received preoperative planned radiotherapy. There was no 30-day operative mortality. A statistically significant higher percentage of at least 1 AE occurred in the LC group (SC, 72.3%; LC, 99.4%; P < 0.001). There were significant differences in favor of SC for grade 3 AE: radiation dermatitis (0% vs 5.6%, P = 0.003), proctitis (0% vs 3.7% P = 0.016), nausea (0% vs 3.1%, P = 0.029), fatigue (0% vs 3.7%, P = 0.016) and grade 3/4 diarrhea rates (1.3% vs 14.2% P < 0.001). No statistically significant differences in surgical complication rates were seen (SC 53.2 vs 50.4% LC, p = 0.68), although permanent stoma (38.0% vs 29.8%, P = 0.13) and anastomotic breakdown (7.1% vs 3.5%, P = 0.26) rates favored LC with perineal wound complications (38.3% vs 50.0%, P = 0.26) in favor of SC. Conclusions: LC had significantly higher AEs compared with SC with no statistically significant differences in postoperative complications. There were clinical trends in permanent stoma rates and anastomotic leaks in favor of LC but with an increased perineal wound breakdown rate.